1998
DOI: 10.1021/es9709886
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Behavior of Fluorescent Whitening Agents in Greifensee:  Field Measurements Combined with Mathematical Modeling of Sedimentation and Photolysis

Abstract: The dynamic behavior of the two fluorescent whitening agents (FWAs) that are currently used in laundry detergents in Switzerland (DAS 1, a diaminostilbene, and DSBP, a distyrylbiphenyl) has been evaluated quantitatively during 1 year for Greifensee, a small lake in Switzerland, by using a one-box model and simulation software (MASAS) for modeling organic pollutants in lakes. Both the onebox model and the one-dimensional simulation were based on (i) independently evaluated processes affecting the fate of FWAs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 15 publications
5
35
0
Order By: Relevance
“…For another hand, it have been found that FWAs are widely distributed in sediment (Managaki and Takada, 2005). While Stoll et al (1998) had ever set a mathematical modeling to analyze the dynamic behavior of FWAs, including photodegradation, sorption/sediment and flushing. All these indicates natural organic matter adsorbed FWAs may be misunderstood as microplastics.…”
mentioning
confidence: 99%
“…For another hand, it have been found that FWAs are widely distributed in sediment (Managaki and Takada, 2005). While Stoll et al (1998) had ever set a mathematical modeling to analyze the dynamic behavior of FWAs, including photodegradation, sorption/sediment and flushing. All these indicates natural organic matter adsorbed FWAs may be misunderstood as microplastics.…”
mentioning
confidence: 99%
“…A well studied example, where direct phototransformation in surface waters is a relevant environmental removal process, are fluorescent whitening agents, a class of high production volume chemicals widely used in laundry detergents and paper and cloth manufacturing [24][25][26][27]. A limited number of QSARs concerning very specific photoreactions, such as the photohydrolysis of aromatic halides [28], have been derived to date.…”
Section: Prediction Of Indirect Phototransformation In Surface Watersmentioning
confidence: 99%
“…This decrease in fluorescence was considered a good indication of the presence of a mixture of FWAs within the water samples (Baker 2002). Sewage disposal is also typically high in FWAs, and numerous studies have utilised these characteristics to trace sewage impact in rivers and lakes (Close et al 1989;Stoll et al 1998;Mostofa et al 2010;Yamaji et al 2010), and the presence of FWAs in sewage is expected to be similar to FWAs which may be present in landfill leachate. The fate of FWAs in groundwater has not been documented in detail.…”
Section: Introductionmentioning
confidence: 99%